Compton Suppression System performance evaluation for measurement of VERDI activation detectors - Anagnostopoulou, Vasiliki; I. Savva, Marilia; Vasilopoulou, Theodora; Mergia, Konstantina; Kokkoris, Michael; Stamatelatos, Ion E. (HNPS Advances in Nuclear Physics, 2023)
The VERDI detector was developed for accurate neutron measurements in the plasma-facing modules of a tokamak. It comprises a low activation capsule, capable to withstand the harsh conditions of the fusion environment, containing a defined mass of metallic foils. The neutron fluence and energy spectrum are derived by analysis of the gamma lines produced by neutron activation of the metallic elements. In this work, the use of a Compton Suppression System (CSS) is investigated aiming to enhance the sensitivity of VERDI detector analysis. The CSS consists of a 40% HPGe primary detector coupled to a set of NaI secondary detectors. The apparatus was set to discard signals simultaneously recorded on both primary and secondary detectors, thus lowering the Compton continuum. The VERDI detectors were irradiated at the Joint European Torus (JET) during the 2019 Deuterium-Deuterium (DD) campaign. The CSS performance was studied by calculating peak and continuum suppression factors. The advantage introduced by Compton suppressed gamma spectrometry for each nuclide of interest is explored and the suitability of this system for VERDI detector measurements is discussed.